Evaluasi Kurikulum Sekolah Menengah Jurusan Akuntansi Menjelang IFRS - Holly Deviarti; Heny Kurniawati (Binus Business Review, 2012)
The changing of financial accounting standard into International Financial Report Standard (IFRS) is the headline for all accountants, for professional public, company and academic accountants. The purpose of this research is to evaluate the curriculum of vocational high school (SMK) accounting major in the advance of applying IFRS. The method used is descriptive explorative approach. This research started through library research, interview with teachers, hold trainings and questionnaire, and analyze the activities. The result showed that SMK in accounting major is not ready yet for the advance of IFRS convergence in 2012, so does the knowledge socialization among teachers and instructors. The researcher recommended holding the preparation for PSAK in IFRS convergence curriculum-based (in cooperation with fostering directorate of vocational high school), training for teachers, arranging accounting books or modules, and adding subjects about IFRS for opening knowledge.